Impact of Blood Disease Bacteria Spread and Economic Losses from Banana Supply Chain Process in Ngada Regency - Mau, Maria Clara; Bao, Antonia Paulina; Uta, Maria Edmunda; Limbu, Umbu N.; Widinugraheni, Sri (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Ngada Regency is one of the regencies in Flores that produces bananas, especially plantains. Kepok banana production has declined over the past four years due to the spread of banana blood disease (BDB). The decrease in harvest yields has resulted in economic losses in the region. This research aims to determine the transportation and distribution mechanisms of banana harvest yields and the handling of bananas in Ngada Regency, the impact of blood disease bacteria on banana transportation and handling, and the economic losses at the farmer producer level, as well as the banana supply chain in Ngada Regency. Additionally, it aims to map the distribution of blood disease bacteria in Ngada Regency. This research employed a qualitative approach using a case study methodology. The data collection techniques in this study consist of three methods: observation, interviews, and documentation. Data from the observation of banana land affected by disease will be displayed in the QGIS mapping program, while data on distribution and transportation mechanisms, handling, economic losses, and the banana supply chain will be analyzed descriptively and qualitatively. The area of banana plantations affected by disease in 2025 is 2,453.21 hectares, covering all areas in Ngada Regency. Traders and distributors supply kepok bananas from the eastern regions of Flores Island, namely Sikka Regency (Maumere) and East Flores Regency (Larantuka), and then sell them to Ngada, Ende, and Manggarai at high prices. Handling of unpackaged bananas is done by covering them directly with tarpaulins during distribution. Banana farmers experienced a drastic economic loss, with a 100% decrease in yield, while traders/collectors saw a 50% decrease in yield and distributors experienced a 63% decrease in yield. The spread of BDB disease has extended throughout the Ngada region, resulting in economic losses for banana farmers, collectors/traders, and distributors. To meet the banana supply chain, bananas are distributed from the Sikka and East Flores Regency.